SIMONA PULKO IN MELITA ZEMLJAK JONTES: SLOVENSKO ALI KNJIŽNO – KAKO JE PRAV? Maribor: Aristej, Slavistično društvo Maribor, 2015. 152 str. - Valh Lopert, Alenka (Slavia Centralis, 2020)
The author presents a scientific monograph by Simona Pulko and Melita Zemljak Jontes, which presents contemporary findings in the field of linguistics on the axis between literary and non-literary in the language use of adolescents.